(untitled) (Bangladesh Journal of Medical Microbiology, 2024)
Background: Different bacteria can cause the chronic suppurative otitis media. Objective: The purpose of the present study was to assess the pattern of bacterial isolates and their antimicrobial susceptibility profiles of chronic suppurative otitis media patients. Methodology: This cross-sectional study was carried in the Department of Microbiology in collaboration with the Department of ENT at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh from July 2017 to June 2018 for a period of one year. In this study, aural swab was taken from patients presented with CSOM and isolation and identification of bacterial species were done by standard microbiological methods. The Kirby Bauer’s modified disc diffusion test was used to determine the antimicrobial susceptibility pattern of the recovered bacterial isolates. Results: Out of 80 ear swabs processed, 42(52.5%) cases were positive by culture and microscopy. No growth was reported in 38 (47.5%) samples. The most commonly isolated bacteria were Pseudomonas aeruginosa followed by Escherichia coli, Staphylococcus aureus, Klebsiella species and Proteus species. Most of the Gram negative bacilli were sensitive to imipenem (100%), meropenem (90.9%), amikacin (85%), gentamicin (72.2%), levofloxacin (60%), azithromycin (52.4%), and ciprofloxacin (52.4%). Gram positive cocci were sensitive to imipenem (100.0%), meropenem (100.0%), amikacin (100.0%), gentamicin (83.3%), ceftriaxone (75.0%), azithromycin (60.0%), erythromycin (50.0%), and ciprofloxacin (28.6%). Conclusion: In conclusion the most commonly isolated bacteria are Pseudomonas aeruginosa followed by Escherichia coli, Staphylococcus aureus, Klebsiella species and Proteus species. Bangladesh Journal of Medical Microbiology, January 2024;18(1):30-36